The “Smart Home” Heat Supply System Based on District Heating with the Utilization of Secondary Energy Resources Using a heat Pump - I. L. Iokova; M. B. Perekhval; I. E. Migutskii (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
One of the most important aspects of a “smart home” is its heating system, which should provide comfortable living conditions for residents while also being energy-efficient. This article discusses an innovative approach to heating systems in “smart homes” based on centralized heating with the utilization of secondary energy resources using a heat pump. The proposed heating system combines the advantages of traditional centralized heating and the efficiency of heat pumps. The article presents a calculated scheme, for which a temperature chart was developed. A methodology for calculating heat loads for both the traditional heating scheme and combined heat and power (CHP) with heat pumps is also proposed, and the necessary calculations were carried out. For clarity of the obtained data, a graph depicting the total steam load required for heating as a function of ambient temperature is constructed, as well as a graph showing the steam load as a function of the duration of the ambient temperature. The analysis of the data revealed that the use of heat pumps in CHP schemes reduces electricity generation by eliminating its production in the steam flow in the condenser. This facilitates the coverage of the electricity consumption schedule during periods of low demand for the integrated energy system. Additionally, integrating a heat pump into the heating system of the centralized heating system helps reduce energy dissipation and greenhouse gas emissions into the atmosphere, making heating more sustainable and environmentally friendly. Moreover, the proposed heating system for a “smart home” demonstrates high technical and economic performance, ensuring the investment attractiveness of such a project.